Smokeless tobacco: Knowledge, attitudes and use among adults in Lagos, South-West, Nigeria - Opanuga OA Ayankogbe OO; Oluwole EO; Odukoya OO (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Background: Smokeless tobacco (SLT) use leads to nicotine addiction and is associated with several health problems. However, it may be perceived as a safe alternative to cigarettes resulting in a potential for increased use among smokers and non-smokers alike. We assessed the pattern of smokeless tobacco use, as well as, the knowledge and attitudes towards SLT among adult residents in Lagos, South West Nigeria. Methods: This was a cross-sectional descriptive study, carried out among 437 respondents selected by a multi-stage sampling method. A modified version of the Global Adult Tobacco Survey Questionnaire was administered to participants by trained research assistants. Data was analyzed using Epi-info statistical software version 3.5.1. Univariate and bivariate analyses were carried out at 5% level of significance (p<.05). Results: The results showed that 47 (10.8%) of the respondents had ever used any form of tobacco. Of these, 29 (6.6% of the total sample and 61.7% of tobacco users) had ever used SLT. Majority of those who had ever used SLT progressed to current use (75.8%). Up to 81.8% of current SLT users were daily users.  SLT use was more common among males (77.3% of current users). Snuff was the most common form of SLT used (81.8% of current SLT users), followed by chewed tobacco (18.2%). Gender and marital status were statistically significant with the current use of SLT (p<.05). However, no significant association was found between knowledge, attitude and SLT use in this study. Many of the respondents knew that SLT is harmful to health (65.4%); causing health issues like discolouration of the teeth (62.2%). However, a much higher proportion of respondents did not know that SLT use was associated with gum disease (50.3%), cancers of the lip (58.8%), tongue (57.4) and gums (58.6%). Overall, only 29.5% had a good knowledge of the health risks associated with SLT use. More than half (66.9%) felt that SLT use was socially acceptable, though 54.7% felt SLT use would be a waste of their money. Overall, 95.1% of respondents had good attitude. SLT use was more among men and those who were divorced/separated or widowed (p<.05). However, respondents knowledge or attitudes was not associated with SLT use. Conclusion: Though SLT use appears relatively low in this environment, the majority of the users used it daily. Progression from initiation to current use was also high. Though the respondents were aware of the general risks associated with SLT use, a significant proportion was unaware of the specific health risks. SLT use was however unrelated to the knowledge of its health risks. Efforts to reduce SLT initiation and progression to current and daily use should be prioritized. A focus on males with marital issues should be considered. Future studies may focus on understanding the underlying reasons for initiation and progression of the SLT use in this environment.